Conflict and Stress Management in Students at Mutiara Bunda Karanganyar Kindergarten - Suyatno, Agus; Sulistyo, Hestuningtyas Adil (Implikasi: Jurnal Manajemen Sumber Daya Manusia, 2023)
This study discusses issues in educational institutions, especially schools related to conflict and stress. This issue must be managed and handled properly so that it does not negatively affect the student development process. The purpose of this study was to determine the application of conflict management in schools and to determine the application of stress management in schools. This study uses a literature study or library research using various journal articles published in the last 10 years. The result is that there is a lot of conflict and stress handling in schools. The treatment technique is considered effective and can significantly reduce anxiety levels, change thinking and behavior and increase positive emotions in them.